Why are European IPOs so rarely priced outside the indicative price range? - Jenkinson, T; Morrison, A; Wilhelm, W (2006)
Unlike in the U.S., the initial price range for European IPOs is seldom revised, although issues are often priced at the upper bound. We develop a model that explains this seemingly inefficient pricing behavior. As in Europe, but not in the U.S., underwriters in the model obtain information from investors before establishing the indicative price range. A commitment to stay within the range is necessary to extract private information from investors. Ours is therefore the first treatment in which the bookbuilding range has a clear economic role. The model has important implications for empirical research based on European primary market data.